Glucocorticoid Exposure Induces Preeclampsia via DampeningLipoxin A4, an Endogenous Anti-Inflammatory and Proresolving Mediator - Liu, Haojing; Huang, Wei; Chen, Liping; Xu, Qiang; Ye, Duyun; Zhang, Dongxin (Frontiers in Pharmacology, 2020)
The pathogenesis of preeclampsia (PE) involves a number of biological processes that may be directly or indirectly affected by glucocorticoid (GC). We demonstrated previously that GC exposure could lead to PE, while PE is associated with a deficiency of lipoxin A4 (LXA4), an endogenous anti-inflammatory and proresolving mediator. The purpose of the present study was to confirm whether GC exposure induces PE via dampening LXA4. In the study, cortisol levels of PE patients were found to be higher than those of non-complicated pregnancies, LXA4 levels were decreased in both PE women and GC-induced PE rats, and leukotriene B4 (LTB4) levels were upregulated in both PE women and GC-induced PE rats. Moreover, cortisol levels were negatively correlated to LXA4 levels, while positively correlated to LTB4 levels in PE patients. Mechanically, GC downregulated LXA4 via disturbing its biosynthetic enzymes, including ALOX15, ALOX5B and ALOX5, especially activating ALOX5, the key enzyme for class switching between LXA4 and LTB4. Importantly, replenishing LXA4 could ameliorate the symptoms and placental oxidative stress of GC-induced rat PE. Moreover, LXA4 could inhibit GC-mediated ALOX5 activation and LTB4 increase, and also suppress 11β-HSD2 expression and corticosterone upregulation. The protective actions of LXA4 might be explained by its roles in antagonizing the effects of GC on trophoblast proliferation and apoptosis. Together, these findings suggest that GC exposure could lead to PE via dampening LXA4, and GC/LXA4 axis might represent a common pathway through which PE occurs.